2016
DOI: 10.1002/cbdv.201600046
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Compounds from the Crop Byproducts of Tunisian Globe Artichoke Cultivars

Abstract: The phytochemical composition in two Tunisian globe artichoke cultivars (bracts, leaves, and floral stems) was evaluated in the plant byproducts. The results indicated that the bracts contain the highest levels of total phenols, o-diphenols, and flavonoids, whereas tannins seem to be more abundant in the leaves. Bracts from the 'Violet d'Hyères' cultivar possessed more total phenols (160.8 mg/g DW), flavonoids (64.9 mg/g DW), and anthocyanins (15.3 μg/g DW) than the 'Blanc d'Oran' bracts (134.5 mg/g DW, 51.2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
11
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
7
11
2
2
Order By: Relevance
“…Similar conclusions were drawn by Dabbou et al . who showed that bracts possess the highest values of total phenols in the studied varieties (160.8 and 134.5 mg hydroxytyrosol equivalents/g DW) for Violet d'Hyères and Blanc d'Oran, respectively) . These authors confirmed that globe artichoke by‐products are rich in phenols with therapeutic activity.…”
Section: Resultssupporting
confidence: 55%
“…Similar conclusions were drawn by Dabbou et al . who showed that bracts possess the highest values of total phenols in the studied varieties (160.8 and 134.5 mg hydroxytyrosol equivalents/g DW) for Violet d'Hyères and Blanc d'Oran, respectively) . These authors confirmed that globe artichoke by‐products are rich in phenols with therapeutic activity.…”
Section: Resultssupporting
confidence: 55%
“…Pandino et al [35] also reported that among the cultivated and wild cultivars studied, the flavonoids content was strongly affected by both cultivar and part of the plant. The contents of tannins found herein in the receptacles of globe artichoke were lower than those of the leaves, bracts, seeds, and stems found in C. cardunculus by other authors;- [10,13,36] nevertheless, no reports have been published on the content of tannins in the receptacles of globe artichoke cultivars in order to make possible a comparison. With regard to the anthocyanins levels, they were higher in 'Blanc d'Oran' (3.7 mg 100 g −1 FW).…”
Section: Phenols Compositioncontrasting
confidence: 62%
“…[8] The globe artichoke also appears as a source of volatile compounds, mainly sesquiterpenes and non-terpenes derivatives as reported by some authors. [9,10] Recently, Claus et al [11] chemically characterized the globe artichoke parts used for protection from oxidative stress in canola oil and reported their fatty acid (FA) content. Moreover, for the receptacle, they reported 88.4 g 100 g −1 of moisture, 12.3 g 100 g −1 of ash, 24.3 g 100 g −1 of crude protein, 1.34 g 100 g −1 of lipids, and 13.1 g 100 g −1 of fibre.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyzing new hybrids and local landraces characterized by bracts with different levels of pigmentation, Bonasia et al [272] observed that "Violetto di Provenza" and "Tempo" characterized by higher pigmentation had also the highest total phenolic content in the heart and external bracts and in the external bracts, respectively. Examining the content of total anthocyanins in bracts, leaves, and floral stems of two genotypes grown in Tunisia, namely "Violet d'Hyéres" and "Blanc d'Oran", Dabbou et al [273] found that leaves of "Blanc d'Oran" had the highest concentration of anthocyanins (20.5 µg/g DW) while bracts and floral stems had the lowest concentration (8.3 and 5.9 µg/g DW, respectively). Instead, lower variability between different plant portions was observed in the case of "Violet d'Hyéres" that on average had a total anthocyanin concentration of 14.2 µg/g DW).…”
Section: Artichokementioning
confidence: 99%